PERILAKU MEROKOK PADA PASIEN TUBERKULOSIS LAKI-LAKI DI KECAMATAN BANYUWANGI, KABUPATEN BANYUWANGI: Smoking Behavior In Men's Tuberculosis Patients In Banyuwangi District, Banyuwangi District - Rahmasuciani Putri; Susy Sebayang; Septa Puspikawati; Erni Astutik (Journal of Community Mental Health and Public Policy, 2019)
An increasing number of smokers is associated with an increased risk of tuberculosis (TB). The risk of TB can be reduced by two thirds if someone stops smoking. The purpose of this study was to determine smoking behavior in TB patients in three puskesmas in Banyuwangi District (Puskesmas Sobo, Puskesmas Kertosari, and Puskesmas Singotrunan). This research is a descriptive study with a cross-sectional approach, which was conducted for 6 (six) months, June to December 2017. This study used data from a study entitled "nutrition status, social support, and health-related quality of life in tuberculosis patients at the center Banyuwangi health services ". Data were collected by conducting a survey using a questionnaire to 71 TB patients, but only male TB patients (56.3%) were further investigated. The results of this study showed 15% of male TB patients continued to smoke, 7.5% smoked daily and 7.5% smoked occasionally. Of the male TB patients who do not currently smoke, 73% smoked daily, and 9% smoked occasionally. As many as 85% of male TB patients have smoked, 4% smoked 5 minutes after waking up, and 21% smoked 6 to 30 minutes after waking up. As many as 11% of male TB patients who smoke spend more than 31 cigarettes, and 14% use 21 to 30 cigarettes. It can be concluded that there are still male TB patients who continue to smoke. The results of this study indicate that the need for empowerment of the PMO (Drugs Supervisor) to monitor smoking behavior in TB patients, counseling in TB patients should be able to detect the existence of addiction to smoking and consultation efforts to stop smoking.